Valdosta Symphony Guild. 26th Season. 2015-2016. - (:unkn) unknown (My University, 2016)
Valdosta Symphony Guild. 26th Season. 2015-2016 -- Calendar of Events -- Letter for the start of the season -- Valdosta Times article "Symphony prepares for 26th season" by Dean Poling -- "New Performing arts seasons arrives" -- "String Project begins Sept 9" -- Guild at a Glance -- Meetup during Summer with photos -- League of American Orchestras Conference: Report to Valdosta Symphony Guild by Emily Rogers -- September Meeting Agenda -- VSG Proudly Supports these Programs list -- September 2015 meeting photos -- Booklet for 2015-2016 season -- Youth Concert: "The Distinctive Voice" information and pamphlet -- Symphony Notes: Meet the Artist: Jennifer Frautschi -- Pre-concert Dinner invitation and article "Violinist ready for concerto's challenges" -- Photographs -- Black and White Ball Sponsors (2014) -- "Pops in the Park" [Andrew Hill: vocalist; Justin Powell: trumpet; Paul Campiglia: director of Steel Drum Band; Joren Cain: director of New Jazz Ensemble; Carol Krueger: director of Spotlighters; David Springfield: director of Jazz Ensemble] -- November meeting agenda -- Photographs -- Symphony Ball: Baubles, Bangles, and Beads -- article "VSO's concert no Brahms lullaby: Renowned pianist performs complex piece" by Dean Poling -- The Rotary Club Recent Programs -- Youth Concert: "The Stirring of the Soul" [Simone Dinnerstein: piano] -- Symphony Notes: Meet the Artist: Simone Dinnerstein -- Letter for accepting Ball invitation -- Auction lists -- "Valdosta Symphony Guild holding its annual ball" and booklet for ball -- Photographs -- Valdosta Magazine cover [Winter 2016; Volume 19, No. 4] -- Valdosta Seen: Symphony Ball and Auction -- Valdosta Daily Times articles: "Nutcracker Performs this weekend"; "Orchestra elects board members"; Guild hosts Tunes for Tots" -- articles "String Project, Youth Orchestra perform Dec. 7"; "Tunes for Tots: children meet instruments" by Desiree Carver -- Calendar of Events (Spring 2016) -- January meeting minutes -- Photographs -- February meeting minutes -- Valdosta Times article "Composing a 'World House': Orchestra host world premier" by Dean Poling -- Symphony Notes: Meet the Artists: Carla Amancio; Andre Valladon; Fhillipe Teixeira -- Youth Concert: "The Art of Expression" [Sarah Wildes Arnett; Eric Brandt Nielsen; Libby McCrary; Carla Amancio; Randolph Lee] -- Photographs -- Pre-concert Dinner Invitation with photographs -- Program continued -- The World House Concerto -- Symphony Notes: Meet the Artists: Carol Krueger; Kristin Schwecker] -- "Symphony plays Mozart's 'Requiem'" by Dean Poling -- Resale Fundraiser -- Barganza Preview Party invitation with photographs -- Symphony Notes: Meet the Composer: Gustav Mahler -- "Orchestra ready for the majesty of Mahler" by Dean Poling -- Annual Luncheon and Champagne Breakfast invitations --
Digitized from original print, Valdosta State University Archives and Special Collections, June 25, 2019.